Exploring the experiences of healthcare professionals in South Africa and Uganda around communicating with children about life-threatening conditions: a workshop-based qualitative study to inform the adaptation of communication frameworks for use in these settings - Elizabeth Rapa; Jeffrey R Hanna; Teresa Pollard; Stephanie Santos-Paulo; Yasmin Gogay; Julia Ambler; Elizabeth Namukwaya; David Kavuma; Elizabeth Nabirye; Ruth Mary Kemigisha; Juliet Namyeso; Tracey Brand; et al. (My University, 2022)
Objectives This study aimed to explore how published communication frameworks could be amended to ensure applicability and cultural appropriateness for professionals to support family-centred conversations by investigating’ healthcare professionals’ (1) experiences of providing support to families when a caregiver or a dependent child (<18 years old) has a life-threatening condition, (2) perceived challenges for caregivers and healthcare professionals in communicating with children about illness, (3) perceptions of how clinicians could be equipped to facilitate conversations between caregivers and children about an adult or the child’s own life-threatening condition and (4) suggestions for amendments to previously published guidelines to ensure cultural relevance in South Africa and Uganda. Design A qualitative study involving two 2-day workshops with embedded focus group discussions, break out rooms and consensus discussions. Setting Health and social care and third sector organisations in South Africa and Uganda. Participants Thirty-two professionals providing care to families affected by life-threatening conditions in South Africa or Uganda who were aged 18 years or older and able to converse in English. Results Participants identified obstacles to having conversations with caregivers about children and to telling children about serious illness during consultations. These included patients’ beliefs about illness, medicine and death, language barriers between families and the healthcare team, and emotional and practical challenges for professionals in having these conversations. Culturally appropriate adaptations were made to previously published communication frameworks for professionals to support family-centred conversations. Conclusions Culturally sensitive communication frameworks could help healthcare professionals to talk with families about what children need to know when they or a caregiver have a serious illness. More broadly, effective communication could be facilitated by promoting healthcare professionals’ and communities’ understanding of the benefits of telling children about illness within the family. Together these strategies may mitigate the psychological impact of global disease on children and their families